Male skirts: a interdisciplinary project through art, design, handicraft and fashion (Revista de Ensino em Artes, Moda e Design, 2021)
This article aims to report and discuss an interdisciplinary activity carriedout during the first academic period in an undergraduate course in Fashion Design between the disciplines of Fashion History and Clothing, Fundamentals and History of Design, Modeling and Fashion Design. This practice mobilized knowledge of art,crafts and fashion in the development of men's skirts presented in the form of a fashion show. As a result, it is discussed how the integration of knowledge is relevant for designers in training so that they understand design in a critical, reflective andintegrative way, translating artistic, craft and technological knowledge into theproducts designed.
Keywords: Interdisciplinarity; Fashion design; Men's skirts